Guilt-free shopping? Second-hand fashion and the sustainability paradox - Rosely, Nurhidayah; Abdullah Thani, Ayu Kamareenna; Ismail, An Nur Nabila; Nik Mohd Zainordin, Nik Mohamad Shamim; Muhamad, Mira Qerul Barriah; Ahmad, Nur Azreen Farihah (Journal of Islamic, Social, Economics and Development, 2026)
Secondhand fashion is widely promoted as a sustainable solution to fashion goods overproduction and waste by extending product lifespans and supporting circular resource flows. However, limited attention has been given to how consumers experience and rationalise secondhand fashion consumption in everyday life. This study explores the meanings and behavioural patterns associated with secondhand fashion consumption among young adult Muslim consumers in Malaysia, with particular attention to its implications for sustainable consumption. Adopting a phenomenological research design, twelve in-depth interviews were conducted and analysed using inductive thematic analysis. The findings reveal that secondhand fashion consumption is frequently framed as a guilt-free and morally acceptable practice, enabling consumers to justify increased acquisition, emotional shopping, and wardrobe expansion. Rather than reducing overall consumption, secondhand markets can function as a psychological buffer that alleviates guilt while sustaining high consumption intensity. This paradox highlights how sustainability-oriented practices may unintentionally enable overconsumption through moral justification and cognitive rationalisation. By revealing the lived tensions between sustainability ideals and consumption behaviour, this study contributes to sustainability science by critically examining demand-side dynamics within circular fashion systems. The findings offer important implications for policymakers, sustainability advocates, and platform designers seeking to promote responsible consumption beyond recycling and resale, aligning with the broader goals of sustainable resource utilisation under SDG 12.